Initial growth phase of W-fuzz formation in ultra-long pulse helium discharge in LHD. (August 2017) - Tokitani, M.; Masuzaki, S.; Kasahara, H.; Yoshimura, Y.; Sakamoto, R.; Yoshida, N.; Ueda, Y.; Mutoh, T.; Nagata, S.
Highlights: Formation of the initial growth phase of the tungsten fiberform nanostructure (W-fuzz) was demonstrated by exposing the bulk tungsten specimen to the LHD divertor plasma during ultra-long pulse helium discharges. The finest W-fuzz structure was able to be identified on the central region of the divertor strike point. Formation of the fuzzy structure was sensitive to the conditions such as tungsten temperature and helium flux. Abstract: In order to confirm the formation of a tungsten fiberform nanostructure (W-fuzz) by helium plasma exposure in the large-sized plasma confinement device, the bulk tungsten with the size of 80 × 20 × 1.5 mm 3 was inserted into the divertor leg position in the Large Helical Device (LHD). Then, it was exposed to the divertor plasma during the ultra-long pulse helium discharges with 10, 190 s in total. The width of the divertor plasma, incident ion energy and total fluence were expected to be ∼2 cm, 100–200 eV and ∼5 × 10 25 He/m 2 (strike position), respectively. The surface temperature of the tungsten specimen was monitored by IR camera. The typical surface temperature of the divertor strike point was estimated to be around 1900 ∼ 2300 K. After the exposure, an initial growth phase of tungsten fiberform nanostructure (W-fuzz) was able to be identified on the tungsten surface. The finest initial growth phase of the W-fuzz structure was able to be identified on the central region of the divertor strike point, where retention amount of helium was estimated to be ∼8 × 10 21 He/m 2 . This study is the first simultaneous evaluation of the W-fuzz growth and quantification of the helium retention in the large-sized plasma confinement device.